Video-Based Learning in Heat Exchanger System: From Conceptual Understanding, Higher-Order Thinking, and Cognitive Analysis to Reducing Misconceptions Among Vocational Students in Support of the SDGs - Nandiyanto, Asep Bayu Dani; Aay Susilawati,; Obie Farobie,; Do’stnazar Ximmateliyev,; Saodat Khamidovna Gayupova, (Journal of Technical Education and Training, 2026)
This study investigates the effectiveness of a video-based learning approach in improving vocational high school students’ conceptual understanding of heat exchanger systems. The research addresses persistent challenges in teaching abstract thermodynamic concepts, particularly students’ misconceptions and difficulties in higher-order thinking. A quasi-experimental design was employed involving experimental and control groups. Data were collected through pretest and posttest assessments and analyzed using normalized gain (N-gain), statistical tests, item-level analysis based on Bloom’s taxonomy, and misconception analysis using the Certainty of Response Index (CRI), along with effect size analysis (Cohen’s d) to determine the magnitude of the intervention effect. The experimental group achieved significantly higher learning gains compared to the control group, with statistically significant improvement and a large practical effect, indicating a substantial impact on students’ conceptual understanding. Item-level analysis revealed that learning improvement in the experimental group extended across both lower-order (C2) and higher-order (C3–C4) cognitive levels. Furthermore, CRI analysis indicated a substantial increase in sound understanding and a significant reduction in misconceptions. However, some non-intuitive concepts, particularly those involving system analysis and flow rate, remained challenging. Overall, the findings demonstrate that video-based learning is effective not only in improving learning outcomes but also in facilitating conceptual change and reducing misconceptions. This study highlights the potential of multimedia-based instruction in enhancing higher-order thinking and supporting more meaningful learning in vocational engineering education, while also contributing to Sustainable Development Goals (SDGs).